A novel thermoresponsive membrane as potential material for tissue engineering. Issue 5 (9th April 2021) - Li, Na; Zheng, Zexiang; Cai, Xiang; Liu, Qiao; Zhang, Yifan; Zhou, Changren; Li, Lihua; Zhao, Yaowu
ABSTRACT: In this study, a thermoresponsive cholesteric liquid crystal (TCLC) was successfully fabricated from a binary mixture of cholesteryl nonanoate (CN) and cholesteryl oleyl carbonate (COC) at different ratios. Furthermore, blends of TCLC and polyurethane (PU) with different weight ratios were prepared by spin coating. Moreover, the mesomorphic temperature ranges of TCLC and TCLC/PU membranes were discussed, and their physicochemical properties were systematically studied by differential scanning calorimetry (DSC) and polarizing optical microscopy (POM) equipped with a heating stage. In addition, the interaction of cells with the TCLC/PU membranes was studied and correlated with the liquid crystal alignment behaviors on the blend films. The results revealed that the different weight ratios of CN and COC determined the liquid crystal properties of the membranes and that the presence of TCLC was essential for metabolizing MC3T3-E1 cells. The biophysical expression of cells on biocompatible blend membranes suggested that TCLC/PU membranes could be a new class of biologically relevant materials. Graphical abstract: